2019
DOI: 10.3390/diagnostics9040172
|View full text |Cite
|
Sign up to set email alerts
|

Acute Bronchiolitis: Is There a Role for Lung Ultrasound?

Abstract: Introduction: Viral bronchiolitis is a common cause of lower respiratory tract infection in the first year of life, considered a health burden because of its morbidity and costs. Its diagnosis is based on history and physical examination and the role of radiographic examination is limited to atypical cases. Thus far, Lung Ultrasound (LUS) is not considered in the diagnostic algorithm for bronchiolitis. Methods: PubMed database was searched for trials reporting on lung ultrasound examination and involving infan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…In this regard, a review evaluated the role of LUS in infants with bronchiolitis. 30 Eight studies were included, and the most common findings ranged from alveolar-interstitial syndrome (confluent vertical artifacts) in mild-to-moderate cases, to subpleural consolidations, areas of white lung, pleural line anomalies, and pleural effusions in the most severe ones. However, as described in our study, the presence of multiple lung artifacts (currently described as alveolar interstitial syndrome) should not reflexively be interpreted as a pathologic finding in this age group, given the prevalence of these findings in otherwise healthy infants, whereas pleural abnormalities, consolidations, and effusion were not noted in healthy infants and remain indicative of a pathologic condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, a review evaluated the role of LUS in infants with bronchiolitis. 30 Eight studies were included, and the most common findings ranged from alveolar-interstitial syndrome (confluent vertical artifacts) in mild-to-moderate cases, to subpleural consolidations, areas of white lung, pleural line anomalies, and pleural effusions in the most severe ones. However, as described in our study, the presence of multiple lung artifacts (currently described as alveolar interstitial syndrome) should not reflexively be interpreted as a pathologic finding in this age group, given the prevalence of these findings in otherwise healthy infants, whereas pleural abnormalities, consolidations, and effusion were not noted in healthy infants and remain indicative of a pathologic condition.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated its usefulness in the diagnosis and follow‐up of community‐acquired pneumonia 27,28 and, in particular, bronchiolitis, 5,29 one of the most common reasons for the seeking of medical care for infants in the first year of life. In this regard, a review evaluated the role of LUS in infants with bronchiolitis 30 . Eight studies were included, and the most common findings ranged from alveolar‐interstitial syndrome (confluent vertical artifacts) in mild‐to‐moderate cases, to subpleural consolidations, areas of white lung, pleural line anomalies, and pleural effusions in the most severe ones.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Jaszczolt et al point out the utility of LUS in comparison with CXR, considering the main advantages of sonographic imaging: absence of radiations, short time of examination, higher sensitivity in the evaluation of pleural effusion, small consolidations and signs of interstitial involvement in patients with bronchiolitis [ 14 ]. In recent decades, many studies suggested that LUS findings in children with bronchiolitis correlate with disease severity [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…72,73 Currently, LUS is not routinely used in the assessment of children with suspected bronchiolitis. [9][10][11]37,38,74 Though often relatively small, the available studies on LUS in cases of bronchiolitis demonstrate common findings include focal or confluent B-lines, subpleural consolidations of variable sizes (with or without air bronchograms), and an irregular pleural line. 10,11 The presence of LUS findings typically increase with a higher disease severity, and LUS has been shown to predict the need for respiratory support.…”
Section: Bronchiolitismentioning
confidence: 99%